Plumbagin, a biomolecule with (anti)osteoclastic properties - Sultanli, Sevinj; Ghumnani, Soni; Ashma, Richa; Hieke-Kubatzky, Katharina (International journal of molecular sciences, 2021)
Plumbagin is a plant-derived naphthoquinone that is widely used in traditional Asian medicine due to its anti-inflammatory and anti-microbial properties. Additionally, plumbagin is cytotoxic for cancer cells due to its ability to trigger reactive oxygen species (ROS) formation and subsequent apoptosis. Since it was reported that plumbagin may inhibit the differentiation of bone resorbing osteoclasts in cancer-related models, we wanted to elucidate whether plumbagin interferes with cytokine-induced osteoclastogenesis. Using C57BL/6 mice, we unexpectedly found that plumbagin treatment enhanced osteoclast formation and that this effect was most pronounced when cells were pre-treated for 24 h with plumbagin before subsequent M-CSF/RANKL stimulation. Plumbagin caused a fast induction of NFATc1 signalling and mTOR-dependent activation of p70S6 kinase which resulted in the initiation of protein translation. In line with this finding, we observed an increase in RANK surface expression after Plumbagin stimulation that enhanced the responsiveness for subsequent RANKL treatment. However, in Balb/c mice and Balb/c-derived RAW264.7 macrophages, these findings could not be corroborated and osteoclastogenesis was inhibited. Our results suggest that the effects of plumbagin depend on the model system used and can therefore either trigger or inhibit osteoclast formation.
Gesehen am 14.04.2021